2014
DOI: 10.1002/lite.201400059
|View full text |Cite
|
Sign up to set email alerts
|

Authentication of borage oil

Abstract: Over the past 30 years borage (Borago officinalis) has become established as a speciality oilseed crop grown exclusively for its oil, a rich source of gamma linolenic acid (GLA), C18 : 3n – 6. GLA is metabolised in the human body from linoleic acid and is itself a precursor in the formation of dihomo‐gammalinolenic acid, arachidonic acid and metabolites of these, prostaglandins, leukotrienes and thromboxanes. The oil is used extensively in the nutritional supplements, cosmetics and pet care industries primaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In turn, evening primrose oil analysed by Montserrat-de la Paz, Fernandez-Arche, Angel-Martin, and Garcia-Gimenez (2014) characterized by 73.88% of linoleic acid and 9.24% γ-linolenic acid. Scrimgeour and Clough (2014) reported that borage oil is an economic source of γ-linolenic acid (GLA). This is due to the highest content of this acid compared to other plant oils.…”
Section: Fatty Acid Composition and Bioactive Compounds Content Of Crmentioning
confidence: 99%
“…In turn, evening primrose oil analysed by Montserrat-de la Paz, Fernandez-Arche, Angel-Martin, and Garcia-Gimenez (2014) characterized by 73.88% of linoleic acid and 9.24% γ-linolenic acid. Scrimgeour and Clough (2014) reported that borage oil is an economic source of γ-linolenic acid (GLA). This is due to the highest content of this acid compared to other plant oils.…”
Section: Fatty Acid Composition and Bioactive Compounds Content Of Crmentioning
confidence: 99%
“…‫کشد‬ ‫اؿبسُ‬ (Moore et al, 2000;Zaborina et al, 2006;Hertel et al, 2015;Carrel et al, 2015;Stewart et al, 2015) . ‫اػت‬ ‫ؿذُ‬ ‫گضاسؽ‬ (Sabour et al, 2015 (Turker & Yıldırım, 2013) ، Borage officinalis ‫اسٍپب‬ ‫دس‬ (Miceli et al, 2014;Scrimgeour & Clough, 2014) …”
mentioning
confidence: 99%